2018
DOI: 10.1155/2018/7042693
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Analysis on Crystallization of Tunnel Drainage Pipes in Chongqing

Abstract: A lot of crystallizations exist on the inner wall of tunnel drainage pipes in Chongqing. Tunnel support structure often bears larger load than usual because the tunnel drainage pipes are blocked easily by the crystals and the groundwater level would rise. In order to investigate what the crystals are, site investigations and laboratory tests of crystals and groundwater were completed. Some valuable results have been obtained. Firstly, the crystallizations are usually discovered in drainage pipe exits of tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…The cross section of the research pipe is semicircle. Flocking drainage pipe has a villi (nylon wire) diameter of 1 mm, longitudinal spacing of 25 mm, and circumferential spacing of 8.72 mm (10 ). The solution required for the test was prepared according to the ratio of m (CaCl 2 ):m (NaHCO 3 ):m(H 2 O) to 1:3:10 of analytical pure calcium chloride reagent and sodium bicarbonate reagent.…”
Section: Experiments Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross section of the research pipe is semicircle. Flocking drainage pipe has a villi (nylon wire) diameter of 1 mm, longitudinal spacing of 25 mm, and circumferential spacing of 8.72 mm (10 ). The solution required for the test was prepared according to the ratio of m (CaCl 2 ):m (NaHCO 3 ):m(H 2 O) to 1:3:10 of analytical pure calcium chloride reagent and sodium bicarbonate reagent.…”
Section: Experiments Designmentioning
confidence: 99%
“…Liu et al 9 analyzed the change rule of the external water pressure of the lining after the unsymmetrical blockage of the drainage system of the tunnel. Zhang et al 10 and Zhou et al 11 carried out a large number of field investigations on the drainage pipe plugging by crystallization, thus determined that the main component of crystallization was calcite crystal calcium carbonate through micro analysis, and finally designed a series of laboratory tests on anti-crystallization. Xiang 12 analyzed the stress response of lining after the blocking of blind drain pipes in water-rich tunnels by numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Rinder et al believed that the precipitation produced by the chemical reaction when groundwater flowed through the initial support shotcrete and the crystallization resulting from environmental factors after the solution entered the drainage pipe were the main sources of crystals in the tunnel drainage pipe [7]. Zhang et al found that crystals in the tunnel drainage system were predominantly calcite composed of CaCO 3 [8]. Xiang Kun et al concluded that the pH value of groundwater had a significant impact on the number of crystals, namely, the higher the pH value, the more likely it was to produce crystals in the drainage pipe [2].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the problem of crystallization blockage in the tunnel drainage system, the current focus is mainly on three aspects: the analysis of crystal composition, the analysis of crystallization influencing factors and the technology to prevent crystallization. The main component of the crystalline material of the tunnel drain pipes is insoluble rectangular calcium carbonate crystals [4][5][6] such as calcite crystal, and the calcium element in the crystal is derived from the groundwater [4,7] in the tunnel and the cement [8] in the shotcrete. The main influencing factors of crystallization-induced blockage include CO 2 partial pressure, flow velocity, temperature, pH, ion type and concentration [9,10].…”
Section: Introductionmentioning
confidence: 99%